Perang Geger Sepehi di Kesultanan Yogyakarta Tahun 1812 M: Prespektif Strategi Militer - Rizky Budi Prasetya Sulton; Syamsunasir Syamsunasir; Bayu Setiawan (IAIN Syekh Nurjati Cirebon, 2022)
This paper discusses the attacks carried out by the British Colonial Government in Java with the Sultanate of Yogyakarta Hadiningrat which occurred from July 18 to July 20, 1812 AD. This study uses historical research methods that emphasize heuristic processes, verification, interpretation, and historiography. The results of this study explain that the background of the conflict originated from the unwillingness of Sultan Hamengkubuwono II to submit to the demands of Lieutenant Governor Raffles fully to the rules and political power of the British Empire in colonies. The strategy of the Sultanate of Yogyakarta was to consolidate regular troops and other troops to defend the Keraton and build military facilities by building weapons factories independently. The British took advantage of their indigenous allies, although they were few in number, with experience and qualified military capacity, they succeeded in controlling Yogyakarta.